Inter-relationships between ADHD, ODD and impulsivity dimensions in emerging adults revealed by network analysis: extending the 'trait impulsivity hypothesis'. Issue 10 (October 2022) - Gomez, Rapson; Stavropoulos, Vasileios; Watson, Shaun; Brown, Taylor; Chen, Wai
Abstract: Background: The trait-impulsivity hypothesis posits impulsivity as the underlying substrate of Attention-deficit/hyperactivity disorder (ADHD) and Oppositional defiant disorder (ODD) symptom expressions. The current study applied network analysis to evaluate the inter-relationships of dimensions within ADHD (inattention and hyperactivity/impulsivity) and ODD (anger/irritable, vindictiveness, and argumentative/defiant behavior) with components of impulsivity as captured by the UPPS-P model (negative urgency, lack of premeditation, lack of perseverance, sensation seeking, and positive urgency). Method: A total of 324 emerging adults (women = 246) from the general community completed questionnaires covering these dimensions. Results: Our findings showed that the ADHD and ODD dimensions were associated differentially with different types of impulsivity, in their unique patterns of network connectivities, a possibility that has had little attention in the trait-impulsivity hypothesis literature. Conclusions: This study is the first to tease out the unique associations of the ADHD and ODD dimensions with different types of impulsivity, and in that way provide new contributions to our understanding of the existing trait impulsivity theory. Our findings would be especially relevant to those interested in understanding how different dimensions of trait impulsivity underly the ADHD and ODD dimensions. Abstract : Trait-impulsivity etiological model; Attention-deficit/hyperactivity disorder; Oppositional defiant disorder; UPPS-P model of impulsive personality; Emerging adults.